The application of Mnemonic Keyword Method on learners’ comprehension and knowledge retention - Ismail, Shaira; Abd Rahman, Nurul Hayani; Shafie, Nani Ilyana; Mohamed, Baderisang (Academica Press Solutions, 2023)
The Mnemonic Keyword Method offers the most potential for use in classroom teaching and learning activities. It encodes the information so that it can be more easily retrieved, and the sentences are transformed into catchy and simple formulas. The method typically involves relating the term to other words or grouping the words according to similar themes or synonyms. The world's phonological or spelling forms are used to construct equations or formulas. The factual component of the knowledge dimension can contain the fundamental concepts that students need to understand to become familiar with any subject. They will also be expected to tackle challenges in the learning process. This method has been successfully increased students' comprehension levels and their capacity to retain the main details of the reading materials they are exposed to learning the Fundamentals of Entrepreneurship (ENT300). The guidelines and directory of keyword offer commercialization potential. The creation of a website with applications to transform the sentences into keywords would be able to generate income via subscriptions. The potential customers are the education providers and students.